The Effectiveness of A or Code-Assisted Water Cycle Diorama Augmented Reality in Improving the Cognitive Learning Outcomes of Grade V Students at Gamping State Elementary School - Shafira Shafira; Suryandari Suryandari; An-Nisa Apriani; Ismanto Ismanto (IJCAR: Indonesian Journal of Classroom Action Research, 2026)
Observation results in grade V of Gamping Public Elementary School on March 14, 2025 showed that science learning was still less than optimal. As many as 8 out of 20 students had not reached the KKM of 70, and their cognitive abilities tended to stop at the C1 (remembering) domain, not yet developing to C2 (understanding), C3 (applying), or C4 (analyzing). This study aims to determine the effectiveness of the Water Cycle Diorama assisted by QR Code Augmented Reality in improving students' cognitive science learning outcomes. This diorama media is designed to help students understand the concept of the water cycle through real, contextual and interactive visualizations, so it is expected to improve their cognitive learning outcomes. This research uses a quantitative research type with a descriptive design.one group pretest and posttest. The research subjects were fifth grade students of SDN Gamping Teknik and the data collection instruments were in the form of learning observation sheets, tests (pretest and posttest). Data validation techniques include content validity tests and empirical validity (content validity tests, reliability, level of difficulty of questions, discrimination power. The data analysis techniques used are normality, and hypothesis testing (t-test and N-Gain) through the SPSS Version 25 program. The results of the t-test in the t-test column for Equality of Means if the Sig. (2-tailed) value is > 0.05 then Ha is rejected and H0 is accepted, meaning there is no significant difference between the results pretest And posttest. On the other hand, if the Sig. (2-tailed) value is < 0.05 then Ha is accepted and H0 is rejected, which means there is a significant difference between the pretest and posttest results. In other words, the use of the Water Cycle Diorama based on QR Code Augmented Reality has a significant influence on improving students' cognitive learning outcomes in science. The results of the study showed that the water cycle diorama learning media assisted by QR Code Augmented Reality was proven effective in improving the cognitive learning outcomes of fifth grade students of Gamping Elementary School in science learning. This was proven by the results of the t-test calculation which showed a significance value (2-tailed) of 0.000 <0.005 which means there was a difference between the pretest and posttest results after learning using the water cycle diorama assisted by QR Code Augmented Reality. In addition, the results of the N-Gain calculation of 0.365870 showed that the increase in learning outcomes was in the moderate category. Thus, the QR Code Augmented Reality assisted diorama media was effectively used in learning to improve the cognitive learning outcomes of fifth grade students of elementary school on the water cycle material.